STUDI PENGARUH TEMPERATUR TERHADAP KEKUATAN TARIK NiTi NANOPILLAR MENGGUNAKAN SIMULASI DINAMIKA MOLEKULER - Septien Tri Cahyono; Rizal Arifin; Munaji Munaji (Universitas Muhammadiyah Ponorogo, 2022)
NiTi alloy is a highly functional alloy of Ni (nickel) metal and Ti (titanium) metal used for engineering. This NiTi alloy has good biocompatibility properties against human body tissues so that currently it is widely used for medical devices. This study aims to determine the effect of temperature on the tensile strength of NiTi Nanopillars and to investigate the behavior of the atoms making up NiTi nanopillars due to tensile loading. From the results obtained, the authors found the greatest value of the modulus of elasticity for the NiTi Nanopillar alloy with a temperature of 100 K, which is 80.4321 GPa. Meanwhile, the lowest modulus of elasticity is the NiTi Nanopillar alloy with a temperature of 600 K, which is 65.5847 GPa. So it can be concluded that the greater the effect of temperature on the NiTi Nanopillar alloy, the smaller the modulus of elasticity will be. This thesis also discusses the stress-strain and mechanical properties of NiTi Nanopillar alloys during the simulation process.